The Herschel Bright Sources (HerBS): sample definition and SCUBA-2 observations. Issue 2 (4th September 2017) - Bakx, Tom J. L. C.; Eales, S. A.; Negrello, M.; Smith, M. W. L.; Valiante, E.; Holland, W. S.; Baes, M.; Bourne, N.; Clements, D. L.; Dannerbauer, H.; De Zotti, G.; Dunne, L.; et al.
Abstract: We present the Herschel Bright Sources (HerBS) sample, a sample of bright, high-redshift Herschel sources detected in the 616.4 deg 2 Herschel Astrophysical Terahertz Large Area Survey. The HerBS sample contains 209 galaxies, selected with a 500 μm flux density greater than 80 mJy and an estimated redshift greater than 2. The sample consists of a combination of hyperluminous infrared galaxies and lensed ultraluminous infrared galaxies during the epoch of peak cosmic star formation. In this paper, we present Submillimetre Common-User Bolometer Array 2 (SCUBA-2) observations at 850 μm of 189 galaxies of the HerBS sample, 152 of these sources were detected. We fit a spectral template to the Herschel -Spectral and Photometric Imaging Receiver (SPIRE) and 850 μm SCUBA-2 flux densities of 22 sources with spectroscopically determined redshifts, using a two-component modified blackbody spectrum as a template. We find a cold- and hot-dust temperature of $21.29_{-1.66}^{+1.35}$ and $45.80_{-3.48}^{+2.88}$  K, a cold-to-hot dust mass ratio of $26.62_{-6.74}^{+5.61}$ and a β of $1.83_{-0.28}^{+0.14}$ . The poor quality of the fit suggests that the sample of galaxies is too diverse to be explained by our simple model. Comparison of our sample to a galaxy evolution model indicates that the fraction of lenses are high. Out of the 152 SCUBA-2 detected galaxies, the model predicts 128.4 ± 2.1 of those galaxies to be lensed (84.5 per cent). The SPIRE 500 μm flux suggests that out of all 209 HerBS sources, we expect 158.1 ± 1.7 lensed sources, giving a total lensing fraction of 76 per cent.